Therapeutic Potential of 7,8-Dimethoxycoumarin in Tumor Necrosis Factor-Alpha-Induced Trigeminal Neuralgia in a Rat Model - Nallupillai Paramakrishnan; Kanthiraj Raadhika; Sumitha Elayaperumal; Yuvaraj Sivamani; Yamunna Paramaswaran; Lim Joe Siang; Thiagharajan Venkata Rathina Kumar; Khian Giap Lim; Muthusamy Ramesh; Arunachalam Muthuraman (Current Issues in Molecular Biology, 2025)
Trigeminal neuralgia is a chronic pain disorder due to neuronal damage. The present study was designed to investigate the effect of 7,8-dimethoxy coumarin (DMC) in a rat model of trigeminal neuralgia. The neuropathic pain was induced by the single endoneural injection of tumor necrosis factor-alpha (TNF-α; 0.1 μL: stock 10 pg/mL) in the rat trigeminal nerve. The DMC (100 and 200 mg/kg) and carbamazepine (100 mg/kg) were administered orally for 10 consecutive days from the 5th day of TNF-α injection. The battery of behavioral tests, i.e., acetone drop and Von Frey filament test, was performed to assess the degree of thermal and mechanical allodynia on 0, 1st, 7th, and 14th days. In addition, the biochemical tests, i.e., total protein, thiobarbituric acid reactive substances (TBARS), reduced glutathione (GSH), and TNF-α, were also performed in trigeminal nerve tissue. Furthermore, TNF-α-induced neuronal histopathological changes were also evaluated by the eosin and hematoxylin staining method. The administration of DMC was shown to demonstrate the significant (p < 0.05) reversal of TNF-α-induced percentage reduction of thermal and mechanical sensitivity, along with a rise in TBARS and TNF-α and a decrease in GSH levels. Further, DMC also attenuates the histopathological changes. It may be concluded that DMC may be a potential therapeutic agent for the management of trigeminal neuralgia disorders.